Self-reactive human CD4 T cell clones form unusual immunological synapses. - Schubert, D; Gordo, S; Sabatino, J; Vardhana, S; Gagnon, E; Sethi, D; Seth, N; Choudhuri, K; Reijonen, H; Nepom, G; Evavold, B; Dustin, M; et al. (2012)
Recognition of self-peptide-MHC (pMHC) complexes by CD4 T cells plays an important role in the pathogenesis of many autoimmune diseases. We analyzed formation of immunological synapses (IS) in self-reactive T cell clones from patients with multiple sclerosis and type 1 diabetes. All self-reactive T cells contained a large number of phosphorylated T cell receptor (TCR) microclusters, indicative of active TCR signaling. However, they showed little or no visible pMHC accumulation or transport of TCR-pMHC complexes into a central supramolecular activation cluster (cSMAC). In contrast, influenza-specific T cells accumulated large quantities of pMHC complexes in microclusters and a cSMAC, even when presented with 100-fold lower pMHC densities. The self-reactive T cells also maintained a high degree of motility, again in sharp contrast to virus-specific T cells. 2D affinity measurements of three of these self-reactive T cell clones demonstrated a normal off-rate but a slow on-rate of TCR binding to pMHC. These unusual IS features may facilitate escape from negative selection by self-reactive T cells encountering very small amounts of self-antigen in the thymus. However, these same features may enable acquisition of effector functions by self-reactive T cells encountering large amounts of self-antigen in the target organ of the autoimmune disease.